Potensi siRNA Terenkapsulasi Nanopartikel sebagai Agen Silencing sflt-1 dan nrf-2: Inovasi Terapi Efektif terhadap Preeklamsia: Inovasi Terapi Efektif terhadap Preeklamsia - Sanjaya Winarta; Raimond Loa; Renaldo Thosal (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2022)
ABSTRACT Background: Maternal death could happen during pregnancy or termination of pregnancy. In 2017, there were around 295.000 maternal death around the world. Indonesia itself is a country with the third largest maternal mortality rate in Southeast Asia. One of the biggest cause of maternal death is preeclampsia. Preeclampsia is usually experienced by pregnant mother with a pregnancy period more than 20 weeks, where there is an elevated blood pressure, proteinuria, and many complications. Nowadays, the only definitive preeclampsia treatment is termination of pregnancy which could cause many bad things to infant, likes preterm birth, intrauterine growth retardation, and intrauterine fetal death. Plenty of reserach shows that small interfering RNA (siRNA) molecule has a potential to become a treatment agent for preeclampsia Therefore, this literature review intends to analyze the potential of siRNA as an innovation of preeclampsia treatment. Method: This literature review was carried out on articles from several databases such as NCBI pubmed, Elsevier, Google Scholar, and Clinical Key with the keywords use are “Nanoparticle”, “Nrf2”, “Preeclampsia”, “sFlt1”, and “siRNA”. Discussion: 6 major journals that correlate with the aim of this literature review were yielded. siRNA molecule can do a silencing to Soluble fms-like tyrosine kinase-1 (sFlt-1) dan Nuclear factor erythroid 2-like 2 (Nrf-2), components that are contribute to pathophysiology of preeclampsia. Furthermore, stabilization of this formulation can be increased by encapsulating the siRNA in a nanoparticle. Conclusion: The formulation of siRNA against sFlt-1 and Nrf-2 can be a novel formulation of therapeutic agent to treat preeclampsia effectively.